Failure of treatment of myasthenia gravis by cyclosporin-A: a case report - Paulo E. Marchiori; J. Lamartine de Assis; Milberto Scaff (Arquivos de Neuro-Psiquiatria, 1989)
Recently, cyclosporin-A (Cy-A) has been used in the treatment oy myasthenia gravis (MG). This drug could be employed in some patients refractory to classic treatments or that develop undesirable side effects. It is reported the case of a 22 year-old woman with generalized and severe MG, and diabetes mellitus. She had been submitted to thymectomy and reoperated, to the classic ethiopathogenic methods of therapy, and to total body irradiation. No therapeutical results were observed. Also, she developed transient and slow bone marrow depression, and liver dysfunction. Owing to these limitations and to the absence of response to treatments mentioned, Cy-A use was attempted in this case. Unfortunately, Cy-A did not influence the myasthenic symptomatology. Cy-A also failed in suppressing anti-AChR production, which increased during Cy-A therapy. Results observed in this case are in disagreement with literature data on the subject.